Calibración de las Protecciones Eléctricas de la Subestación Sarapullo del Proyecto Hidroeléctrico Toachi – Pilatón. - Caizapanta Tapia, Freddy Estalin (2022)
An electrical system that does not have a coordination study of electrical protections can be affected and may not guarantee a correct operation. For this reason, in this research project, the coordination of the overcurrent electrical protections of the S/E Sarapullo - PHTP was overcurrent electrical protections of the S/E Sarapullo - PHTP, which is in the provinces of located between the provinces of Pichincha, Santo Domingo de los Tsáchilas and Cotopaxi. The Sarapullo Substation receives generation through RIP bars, a power of 3 hydro generators of 16.15 [MW] each at 13.8kV level from the Sarapullo Power House, the Sarapullo Powerhouse will also deliver power to the La Palma S/E and to a switchyard where there is a transformer switchyard where there is a 13.8/230 kV step-up transformer to deliver power to a 230 kV L/T, that will reach the Alluriquín substation where it will be connected to the Santa Rosa and Santo Domingo lines of the National Interconnected System (SNI). The electrical characteristics of the system were considered at the electrical characteristics of the system were considered as a starting point for modeling and coordinating the modeling and coordination of the electrical protections of the Sarapullo substation. calculation of short circuit current, the IEC 60909 standard was applied. Using the information provided by the client, we obtained the network equivalent upstream of the Sarapullo substation for the Sarapullo substation to focus the research topic without leaving aside all the parameters of the parameters that make up the Toachi Pilatón Hydroelectric Project and the SNI. The Sarapullo S/E works at 13.8/230 kV levels for which the nominal current at which it will be operating was obtained. A nominal current at which the relays will be operating was obtained. Relays, 20% more than the nominal current was considered for the adjustment of the protection relays. The coordination of the electrical protections considered maximum, and minimum short-circuit currents for, and minimum short-circuit currents for single-phase and three-phase faults. The relays used in the project are numerical relays RED670, REL650, RET670, and REF615. discrimination time between curves was 250ms with a tolerance of +/- 50ms. Most of the IEC Inverse curves were mostly used for single-phase and three-phase fault settings for the three-phase faults; for power transformer protection, bidirectional protections were used. bidirectional protections were used for power transformer protection.